EFEKTIFITAS SAYURAN SELADA (Lactuca sativa L.) DALAM MEREDUKSI KONSENTRASI NITRAT PADA LIMBAH HASIL BUDIDAYA IKAN PATIN (Pangasius pangasius) DENGAN SISTEM AKUAPONIK - ichtiarini nurullita santri; Surahma Asti Mulasari; Oktarianyah Mulasari (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2023)
Background: Water is a natural resource that has a very important function for human life and other living things. Aquaculture waste produces ammonia, nitrite and nitrate waste. Nitrates can have a negative impact on the environment, among others, by contaminating water sources for various purposes, one of which is drinking water and causing health problems for humans. Method: This research used quasi-experimental (Quasi experiment) with Non-Equivalent Control group design. The study involved two groups, the control and the treatment by supplying 108 lettuce planting holes in three times. Data analysis used univariate and bivariate analysis with Wilcoxon test. Result: The lettuce (Lactuca sativa L) had no effect in reduced nitrate concentrations in the posttreatment. The results of the Wilcoxon test showed a p-value of 0.068. Conclusion: There was no significant difference in nitrate concentration in catfish (Pangasius pangasius) culture water at the input and output of the lettuce (Lactuca sativa L) installation.